Essential Role of Transcription Factor Nuclear Factor-κB in Regulation of Interleukin-8 Gene Expression by Nitrite Reductase from Pseudomonas aeruginosa in Respiratory Epithelial Cells - Mori, Naoki (American Society for Microbiology, 1999)
Persistent infection with Pseudomonas aeruginosa increases interleukin-8 (IL-8) levels and causes dense neutrophil infiltrations in the airways of patients with chronic airway diseases. Recently, we have reported that nitrite reductase from P. aeruginosa induces the production of IL-8 in respiratory cells, including bronchial epithelial cells. To determine the molecular mechanism(s) of nitrite reductase-induced IL-8 expression in respiratory cells, A549 epithelial cells were transfected with plasmids containing serial deletions of the 5′-flanking region of the IL-8 gene and then exposed to nitrite reductase. Nitrite reductase significantly enhanced IL-8 gene promoter-driven reporter activity. This increased IL-8 gene expression was inhibited by mutating the nuclear factor-κB (NF-κB) binding element. Nitrite reductase enhanced nuclear localization of the NF-κB binding complex. Furthermore, nitrite reductase induced the degradation of IκBα, the major cytoplasmic inhibitor of NF-κB, and the expression of IκBα mRNA. These data support the critical role of the activation of NF-κB in nitrite reductase-induced IL-8 gene expression in airway epithelium.